Noun Phrases of Jace Waylands Utterances in Mortal Instruments: City of Bones - Dimas Indra Pratama; Arina Istianah (Universitas Sanata Dharma, 2017)
A noun phrase is one of the important elements in building a sentence. Every noun phrase has its own head of the phrase. The structure of the noun phrase can be different according to the modification of the head. There are two kinds of modification to the head of the phrase: pre-modification and post-modification. The existence of the modifiers plays certain roles to the noun phrase. This article presents how the pre-modification affects the character in a literary work. Cassandra Clares Mortal Instruments: City of Bones was chosen as the work to observe. Stylistic approach is used in order to conduct this study. The data of the study is collected from the noun phrases found in one of the characters utterances, Jace Wayland. The analysis presented in this article covers the types of structure, distribution, and function of noun phrases. This study found several results of the analysis. First, there are seven types of noun phrase structure found in the utterances of Jace Wayland. Second, there are four main functions of a noun phrase in a clause: subject, object, prepositional complement, and predicative complement. Third, the noun phrases also have significant role in revealing the character of Jace Wayland: being descriptive and direct.Keywords: noun phrase, stylistics, pre-modification